Penıngkatan Kognitif Bahasa Inggris Sıswa Dengan Pemanfaatan Media Interaktif Berbasis Metode Pembelajaran CAFE (Content, Activities, Facilitating, Evaluation) Menggunakan Permainan Petualangan - Mutohari Mutohari; Suherman Suherman; Isti Rusdiyani (Universitas Mathla'ul Anwar Banten, 2021)
This research aims to proving students' Cognitive English enhancement using interactive multimedia with the utilization of interactive multimedia. This research is carried on the student of 7th class from SMPN 14 Kota Serang. The steps in this multimedia refers to the stages of CAFE learning method. The multimedia development is done through the stages of Research and Development (R&D) method: information gathering, planning, product development, Implementation and assessment. The average score obtained by students at the time of the pretest was 40.41 and the average score obtained by the students at the time of the posttest was 82.34. Based on these results, the average difference between the pretest and posttest values expressed in the gain (G) value is 0.709 with a very good category.